EVALUATION ON THE ANTIHYPERTENSIVE THERAPY USAGE ON BLOOD PRESSURE PREDIALYSIS IN OUTPATIENTS WITH END STAGE RENAL DISEASE (ESRD) RECIVING ROUTINE HEMODIALYSIS AT PKU MUHAMMADIYAH HOSPITAL YOGYAKARTA - Fitriani Fitriani; Agung Endro Nugroho; Inayati Inayati (Faculty of Pharmacy, Universitas Gadjah Mada)
Hypertension and chronic kidney disease (CKD) are the two kinds of disease that are related each others. The prevalence of hypertension is estimated occur in 80% of the hemodialysis population. This research aims to determine the relationship between the compliance levels of patients in antihypertensive medication on blood pressure predialysis This research is conducted by using a descriptive prospective observational study. Data analysis was performed to determine the profile of antihypertensive therapy use, antihypertensive medication therapy outcomes profile, and the influence of the patients’ compliance level in antihypertensive medication. The patient compliance level in taking antihypertensive drugs is assessed by questionnaire of Modified Morisky Scale (MMS). Based on the research results,, the antihypertensive profile used was CCBs system (32,91%), loop diuretics (23,42%), AIIRA (15,82%), central α agonists (12,66%), ACEI (12,03 %), and β blockers (3,16%). Antihypertensive therapies applied single and combination therapy. The most used monotherapy is CCBs (3,70%), whereas the most used combination are combination of the class of CCBs, AIIRA, and loop diuretics (16.67%). The outcomes profile of antihypertensive medication therapy based on the measurement results of pre-dialysis blood pressure are target of pre-dialysis blood pressure (<140/90 mmHg) can only be achieved by 3 patients, 2 patients are the compliance patients with the right choice and appropriate dose of antihypertensive therapy and 1 patient is a non-adherent patient with incorrect type and inappropriate doses of antihypertensive therapy. Most of hemodialysis patients have isolated systolic hypertension. The influence of the patients’ compliance level in antihypertensive medication towards the blood pressure control of pre-dialysis outpatients, there are 19 patients (35,19%) in the category of non-adherent patients with a mean blood pressure is 168,40/ 91,95 mmHg, and 35 patients (64,81%) in the category of adherence with a mean blood pressure is 165,60/ 87,77 mmHg. Keywords : digoxin, heart failure, renal dysfunction, clinical outcome.